Unusual RNA plant virus integration in the soybean genome leads to the production of small RNAs. (May 2016) - da Fonseca, Guilherme Cordenonsi; de Oliveira, Luiz Felipe Valter; de Morais, Guilherme Loss; Abdelnor, Ricardo Vilela; Nepomuceno, Alexandre Lima; Waterhouse, Peter M.; Farinelli, Laurent; Margis, Rogerio
Graphical abstract: Highlights: CMV RNA 1 integration in soybean genome was mediated by a copia-like retrotransposon. CMV RNA 1 was integrated as inverted repeat copies. Active transcription of viral RNA as a hairpin promotes small RNAs production. Nucleotide conservation of CMV RNA 1 suggests a recent horizontal transfer event. Abstract: Horizontal gene transfer (HGT) is known to be a major force in genome evolution. The acquisition of genes from viruses by eukaryotic genomes is a well-studied example of HGT, including rare cases of non-retroviral RNA virus integration. The present study describes the integration of cucumber mosaic virus RNA-1 into soybean genome. After an initial metatranscriptomic analysis of small RNAs derived from soybean, the de novo assembly resulted a 3029-nt contig homologous to RNA-1. The integration of this sequence in the soybean genome was confirmed by DNA deep sequencing. The locus where the integration occurred harbors the full RNA-1 sequence followed by the partial sequence of an endogenous mRNA and another sequence of RNA-1 as an inverted repeat and allowing the formation of a hairpin structure. This region recombined into a retrotransposon located inside an exon of a soybean gene. The nucleotide similarity of the integrated sequence compared to other Cucumber mosaic virus sequences indicates that the integration event occurred recently. We described a rare event of non-retroviral RNA virus integration in soybean that leads to the production of a double-stranded RNA in a similar fashion to virus resistance RNAi plants.